Comparative study of the clinical and anti-microbial efficacy of tongue cleaners - Juliana dos Reis Derceli; Tatiane Arruda Tardivo; Juliana Rico Pires; Elaine Maria Sgavioli Massucato; Silvana Regina Perez Orrico; Denise Madalena Palomari Spolidorio (Universidade Estadual de Campinas, 2016)
Candida species have frequently been isolated from the oral cavities of a variety of patients, such as elderly people, dentures users, immunocompromised and health patients. Yeasts may be associated with immune response and local factors such as poor oral hygiene. It was evaluated effectiveness of tongue cleaner showing which types would be preferred by patients, changes in tongue coating and in saliva yeasts counting. Thirty patients were selected and randomly distributed into three groups. This crossover blind study evaluated the effect of tongue cleaning using: a plastic and a steel tongue scraper and a nylon soft-bristle toothbrush. All patients were instructed to use the cleaners twice a day for one week (fifteen-day wash-out period). Saliva and tongue coating samples were collected from each patient from each test period, the yeasts were counted by colony forming units per mL (CFU/mL) and the species were identified. The patients were questioned about cleaner preference. An increase in the percentage of patients with no tongue coating after scraping was observed. A reduction in the mean number of Candida species in tongue coating was observed only after nylon soft-bristle toothbrush cleaner. Candida albicans was the prevalent species. Volunteers preferred to the steel tongue scraper (60%). Tongue cleaners reduced the tongue coating and the mean number of saliva's yeasts. Degree of tongue coating favors the Candida species colonization